2023
DOI: 10.1007/s10461-023-04150-9
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics and HIV-Related Outcomes of People Living with Co-occurring HIV and Mental Health Conditions in the United States: A Systematic Review of Literature from 2016 to 2021

Thomas O’Grady,
Nina Inman,
Alitasha Younger
et al.

Abstract: Considering advances in HIV prevention and treatment, jurisdictional efforts to end the HIV/AIDS epidemic, and reduced stigma towards people living with HIV infection and mental health conditions, the authors systematically reviewed studies published between 2016 and 2021 and identified 45 studies that met the eligibility criteria. The review found that stigma towards mental health conditions still acts as a barrier to accessing HIV treatment, which impacts treatment outcomes. Additionally, social determinants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Socioeconomic inequalities such as debt [49], lower education level, unemployment [50], and low income [51] are well recognized drivers of poor mental health in the general population. A systematic review of people with HIV in the USA noted multiple social determinants of health to be associated with depression, such as income, housing instability, food insecurity, educational attainment, transactional sex, and low social support [52]; however, individual studies lacked the broad approach used in this study. Syndemic approaches illustrate the complex, mutually reinforcing and converging relationships between SDH and mental health; the Women's Interagency HIV study (WIHS) demonstrated the negative and intersecting influences of depression, food insecurity, violence, and substance misuse on poor HIV outcomes and as drivers for intimate partner violence [53] and highlight the complexity of the interactions between mental health and SDH.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic inequalities such as debt [49], lower education level, unemployment [50], and low income [51] are well recognized drivers of poor mental health in the general population. A systematic review of people with HIV in the USA noted multiple social determinants of health to be associated with depression, such as income, housing instability, food insecurity, educational attainment, transactional sex, and low social support [52]; however, individual studies lacked the broad approach used in this study. Syndemic approaches illustrate the complex, mutually reinforcing and converging relationships between SDH and mental health; the Women's Interagency HIV study (WIHS) demonstrated the negative and intersecting influences of depression, food insecurity, violence, and substance misuse on poor HIV outcomes and as drivers for intimate partner violence [53] and highlight the complexity of the interactions between mental health and SDH.…”
Section: Discussionmentioning
confidence: 99%
“…Across the HIV treatment cascade, mental illness has been associated with poorer outcomes overall, but individuals with SMI in particular have low rates of HIV testing [5], antiretroviral therapy prescriptions [6,7], and viral suppression when compared to the general HIV population [8,9]. Moreover, prior improvements in care across the HIV care continuum (e.g., improvements in viral suppression) have slowed due to the COVID-19 pandemic [10], making it possible that vulnerable subpopulations of PLWH have experienced even further setbacks.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 Syndemics have been described for decades in the HIV literature, and studies continue to demonstrate that the additive power of syndemic factors such as mood disorders, drug use, and stigma, amongst people living with HIV, leads to worse health outcomes. 5 …”
Section: Introductionmentioning
confidence: 99%
“…They are also more likely to have lower engagement in care and experience poorer health outcomes such as decreased viral load suppression and increased mortality. 5 It has been demonstrated that screening for, and treating, substance use disorder within HIV care leads to increased retention in care and improved outcomes on the HIV continuum of care, adding further proof of concept to the application of syndemic theory. 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation